Effect of away goals rule and VAR on game-related statistics in the UEFA women`s champions league - Stone, J. A.; Kubayi, A.; Armatas, V. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Despite significant debate over UEFA`s decision to abolish the away goals rule in 2021 and introduce the use of Video Assistant Refereeing (VAR), little research has considered its potential effects on team performance. Hence, this study investigates how the change in the goals rule and use of (VAR) during the knock phase of UEFA Women`s Champions League affected selected game-related statistics. Data were sourced via the Wyscout platform. The sample consists of 78 UEFA Women`s Champions League knockout round matches; 30 of the matches took place in seasons with the away goals rule (AGR) and no VAR (2016 to 2019) and 48 in seasons without AGR and VAR included (2021 to 2025). Data analysis was performed using a combination of T-Tests; Mann-Whitney-U Tests and Generalised Linear Models. The findings demonstrate that the change in rules resulted in a reductions in the numbers of balls lost (p < 0.01), ball recoveries (p < 0.01), long passes (p < 0.01), forward passes (p < 0.05), passes to the final third (p < 0.01), fouls (p < 0.05), aerial duels (p < 0.01), aerial duels won (p < 0.01), and free kicks (p < 0.01). In contrast, elimination of the away goals rule and inclusion of VAR led to a significant increase in the number of goals (p < 0.05), percentage of accurate passes and counter attacks with shots (p < 0.05). Football governing bodies could consider these findings when deciding whether the rule changes has impacted on the women`s game as expected.